Moderation of Hajj and Umrah Rites in the Armuzna Process for Ensuring the Security and Safety of Pilgrims - Ramadan Subhi; Asnaini Asnaini; Yosi Arisandy (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
One form of religious moderation is Hajj manasik moderation. In the context of Hajj, not excessive attitude is very important because one aspect of Hajj and Umrah is physical worship which requires people who perform it to be in good health. In fact, the physical condition of Hajj pilgrims is very different due to age and health factors. This objective will be explained through 3 (three) questions, namely: 1) how is the implementation of the pillars of Hajj in Armusna from the view of moderation of Hajj and Umrah manasik? 2) What is the purpose of moderation of Hajj manasik in the Armuzna process? 3) What do scholars think about the moderation of Hajj and Umrah? This research is library research  with qualitative research type. The results of the study that moderation in the context of manasik is a solution to help pilgrims who are udzur or have obstacles to be able to carry out worship easily and legally as the opinion of the fuqaha in four madzhabs, namely the Hanafi, Maliki, Shafi'i and Hanbali madzhabs. Manasik moderation especially in the Armuzna process is very important because the three places (Arafat, Muzdalifah and Mina) are the peak of Hajj which requires strong physical and mental energy, with moderation the pilgrims can choose based on several schools for the security and safety of pilgrims